Is there racism in academic medical publishing? - Niriella, M.A.; de Silva, A.P.; de Silva, H.J.; Jayasinghe, S. (BMJ Publishing Group, 2021)
No abstract available.
Indexed in MEDLINE.
Keywords: Racism